For the sake of nature – a study on biodiversity reporting by Dutch listed companies - Karen Maas; Thomas Thijssens; Kavita Nandram (MAB)
As the attention for climate change has grown in recent years, the topic of biodiversity loss has become increasingly relevant. The importance of biodiversity is reflected in the requirements stated in the Corporate Sustainability Reporting Directive (2022). 2024 is the year in which CSRD and ESRS are effective, implying that the first reports that must be compliant (by large listed companies) will be published in 2025. This article reflects on how and to what extent Dutch large listed companies already address the topic of biodiversity in their annual reports one year before they must comply with the CSRD (2024). Our research shows that many companies are aware of biodiversity issues. However, many companies have to further specify their policy, strategy, actions and targets by next year.